Faktor-Faktor yang memengaruhi Nilai Perusahaan pada Perusahaan Non-Keuangan - Vico Vico; Aries Jonathan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This research was conducted to examine the effect of good corporate governance (managerial ownership, board of commissioner, independent commissioner and audit committee), CSR disclosure, dividend policy, and company’s characteristics (profitability, firm size, leverage and liquidity) in affecting firm value in non financial companies listed in Indonesia Stock Exchange. This research used 67 non-financial companies listed in Indonesia Stock Exchange since 2015 until 2017 and selected by purposive sampling method. Multiple linear regression is used to analyze the data in this study. The research results show that the independent commissioner, audit committee, dividend policy, profitability and firm size had influence towards firm value and for the managerial ownership, board of commissioner, CSR disclosure; leverage and liquidity had no influence towards firm value.